Al-Murabit Al-Dalai (d. 1090 AH) methodology of martyrdom in his book (Achievement results in the explanation of the book of facilitation) (Journal of the College of Basic Education, 2022)
The grammatical rule does not heal except with the availability of several principles that are completed after extrapolating the words of the Arabs and following their languages. Because language is a social phenomenon that cannot be issued from a fixed unit whose interactions give one result, similar to non-human sciences, so the difference in data requires a difference in the research methodology, and here comes the task of (the witness) in linguistic studies, especially grammatical, as it is relied upon to provide evidence of refutation or support and affirmation.